Estudo do óleo essencial e extrato hexânico da casca do caule de Schinus lentiscifolius - Ferraz, Adriano (2015)
Many advances in science and industry were inspired by research in natural products, and play an important role in the evolution of organic synthesis, as many methods have been inserted by the efforts in the total synthesis of natural compounds. The few studies with Schinus species lentiscifolius and be widely found in Rio Grande do Sul contributed to their choice as object of study. Using for this purpose the essential oil extracted by hydrodistillation of the stem bark and the hexane extract. The analysis revealed the presence of these basic structures such as α-pinene and myrcene, however, when there is heating the plant material that contain the transformation occurs in more complex structures such as bicyclogermacrene, this turned into during spathulenol isolation process. The study of extract revealed the presence of a mixture of four isomers of similar polarity, requiring esterification to aid in separation. And check of a coupling in the cosy experiment that was not expected, suggesting a change in stereochemistry of morônico acid. Obtained also a metabolite comprises a five-membered lactone with a linear chain substituent comprising sixteen carbons. The originated derivatives morônico acid were an attempt to enhance their antimicrobial activity by inserting a triple bond and later a triazole. The antimicrobial activity revealed that only the morônico acid has a significant activity against the bacteria tested and that the attempt to enhance this activity with derivatives was ineffective.